Cultural imperialism essays on the political economy of cultural domination - Hamm, Bernd 1945-2015; Smandych, Russell Charles (University of Toronto Press, 2019)
What is cultural imperialism? What are the arguments made by critics and apologists of recent well-documented efforts at American global cultural domination? How is cultural imperialism related to neo-liberalism and globalization? Is cultural imperialism a one-way process, or is it inherently recursive, involving many possible reverse cultural flows? How is American, and more broadly Anglo-Western, cultural imperialism revealed in specific cultural institutions, processes, and recent geopolitical global developments, including: the Hollywood motion picture industry and the culturally-homogenizing influence of powerful Western cultural and media industries; the battle over the hearts and minds of the masses during the US-led War on Terrorism; the neo-liberal attack on the humanities; GATS agreements on trade liberalization and the commodification of education; the forced imposition of World Bank-initiated good governance regimes in developing countries; and the current human catastrophe we are experiencing from our seemingly inevitable move toward global ecological destruction? These are some of the many questions answered by the authors in this book.
Keywords: Coursebook; POLITICAL SCIENCE / Political Economy; Kulturimperialismus; Aufsatzsammlung